Counting‐loss correction for X‐ray spectra using the pulse‐repairing method. (9th November 2018) - Tang, Lin; Zhou, Jianbin; Fang, Fang; Yu, Jie; Hong, Xu; Liao, Xianli; Zhou, Chuanwei; Yu, Songke
Abstract : A method is proposed to correct for the counting loss generated by removing distorted pulses in X‐ray spectra. The count rate obtained by the pulse repair method is increased by about 3% compared with that obtained by the pulse elimination method, and the sum of the peak area obtained by the pulse repairing method is increased by about 2.7% compared with that obtained by the pulse elimination method. Abstract : Facing the technical problem of pulse distortion caused by frequent resetting in the latest high‐performance silicon drift detectors, which work under high‐counting‐rate conditions, a method has been used to remove false peaks in order to obtain a precise X‐ray spectrum, the essence of which eliminates distorted pulses. Aiming at solving the problem of counting‐loss generated by eliminating distorted pulses, this paper proposes an improved method of pulse repairing. A 238 Pu source with activity of 10 mCi was used as the measurement object, and the energy spectrum obtained by the pulse repairing method was compared with that obtained by the pulse elimination method. The ten‐measurement results show that the pulse repairing method can correct the counting‐loss caused by the pulse elimination method and increase peak area, which is of great significance for obtaining a precise X‐ray energy spectrum.